2020
DOI: 10.1364/ao.410172
|View full text |Cite
|
Sign up to set email alerts
|

In vivo acoustoelectric imaging for high-resolution visualization of cardiac electric spatiotemporal dynamics

Abstract: Acoustoelectric cardiac imaging (ACI) is a hybrid modality that exploits the interaction of an ultrasonic pressure wave and the resistivity of tissue to map current densities in the heart. This study demonstrates for the first time in vivo ACI in a swine model. ACI measured beat-to-beat variability (n = 20) of the peak of the cardiac activation wave at one location of the left ventricle as 5.32 ± 0.74 ~V, 3.26 ± 0.54 mm below the epicardial surface, and 2.67 ± 0.56 ms before the peak of the local electrogram. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Wang et al then demonstrated the AEI of a time-varying 3D current field based on simulation and phantom experiments (Wang et al, 2011;Wang and Witte, 2014). Recent studies performed AEI in rat, rabbit, and swine hearts to effectively localize the current density distribution (Qin et al, 2015;Berthon et al, 2019;Alvarez et al, 2020). In addition, some works have made a progress in improving AEI performance, such as sensitivity, spatial resolution, and signal-tonoise ratio (Qin et al, 2012;Wang et al, 2016).…”
Section: Related Workmentioning
confidence: 99%
“…Wang et al then demonstrated the AEI of a time-varying 3D current field based on simulation and phantom experiments (Wang et al, 2011;Wang and Witte, 2014). Recent studies performed AEI in rat, rabbit, and swine hearts to effectively localize the current density distribution (Qin et al, 2015;Berthon et al, 2019;Alvarez et al, 2020). In addition, some works have made a progress in improving AEI performance, such as sensitivity, spatial resolution, and signal-tonoise ratio (Qin et al, 2012;Wang et al, 2016).…”
Section: Related Workmentioning
confidence: 99%
“…In addition, he used UCSDI for the first time to map the anatomical potential conduction of the living rabbit heart, which could provide the spatiotemporal distribution of cardiac activation waves (Olafsson et al, 2009 ). Alvarez later demonstrated current source imaging in vivo for the first time in a swine model (Alvarez et al, 2019 , 2020a , b ). Wang also used a pair of electrodes to generate alternating current distributions in a special imaging chamber filled with 0.9% NaCl solution, and obtained time-lapse volume movies of the alternating current distribution ( Figure 5 ) (Wang et al, 2011 ).…”
Section: Research Progressmentioning
confidence: 99%
“…This small elastic deformation induces change in resistivity. The mechanism and methods of AEBI have been fully validated through experiments in previous research [13][14][15][16][17][18]. Recently, researchers have advanced AEBI in different ways and made good progress.…”
Section: Introductionmentioning
confidence: 96%